Upregulated Intrathecal Expression of VEGF-A and Long Lasting Global Upregulation of Proinflammatory Immune Mediators in Vaccine Breakthrough Tick-Borne Encephalitis - Pavletič, Miša; Korva, Misa; Knap, Nataša; Bogovič, Petra; Lusa, Lara; Strle, Klemen; Nahtigal Klevišar, Mirijam; Vovko, Tomaž; Tomažič, Janez; Lotrič-Furlan, Stanka; Strle, Franc; Avšič-Županc, Tatjana (Frontiers in Cellular and Infection Microbiology, 2021)
Although anti-TBE vaccines are highly effective, vaccine breakthrough (VBT) cases have been reported. With increasing evidence for immune system involvement in TBE pathogenesis, we characterized the immune mediators reflecting innate and adaptive T and B cell responses in neurological and convalescent phase in VBT TBE patients. At the beginning of the neurological phase, VBT patients have significantly higher serum levels of several innate and adaptive inflammatory cytokines compared to healthy donors, reflecting a global inflammatory state. The majority of cytokines, particularly those associated with innate and Th1 responses, are highly concentrated in CSF and positively correlate with intrathecal immune cell counts, demonstrating the localization of Th1 and proinflammatory responses in CNS, the site of disease in TBE. Interestingly, compared to unvaccinated TBE patients, VBT TBE patients have significantly higher CSF levels of VEGF-A and IFN-β and higher systemic levels of neutrophil chemoattractants IL-8/CXCL8 and GROα/CXCL1 on admission. Moreover, serum levels of IL-8/CXCL8 and GROα/CXCL1 remain elevated for two months after the onset of neurological symptoms, indicating a prolonged systemic immune activation in VBT patients. These findings provide the first insights into the type of immune responses and their dynamics during TBE in VBT patients. An observed systemic upregulation of neutrophil derived inflammation in acute and convalescent phase of TBE together with highly expressed VEGF-A could contribute to BBB disruption that facilitates the entry of immune cells and supports the intrathecal localization of Th1 responses observed in VBT patients.